On the cyclic yield surface of some engineering materials under complex stress conditions - Dietrich, L.; Kowalewski, Z.L. (Archives of Mechanics, 1998)
The paper presents a new method of mechanical parameters analysis. It deals with determination of a "cyclic yield surface" for selected engineering materials on the basis of cyclic curves experimentally obtained under a complex stress state. Location of the cyclic yield surface with respect to that of the initial yield locus may constitute the basis for evaluation of the material sensitivity to the cyclic deformation. Tests have been carried out with the use of PA6 aluminium alloy and 18G2A low-alloy steel, both in the as-received state. The experimental programme was the same for both considered materials. Firstly, an initial yield surface was determined using a number of specimens which were loaded up to the plastic range along different loading paths. Secondly, cyclic predeformations due to various loading paths in the plane stress state were induced by cyclic loading at ambient temperature under constant (Δε = ±0.65%) and gradually decreasing strain amplitude (from Δε = ±0.65% to 0%). Finally, subsequent yield surfaces were determined using the single specimen method. It is shown that depending on the material, a cyclic loading induces softening (low-alloy steel) or hardening (aluminium alloy) effect in the strain range considered. All differences in material responses to cyclic prestraining for the tested materials are discussed in detail.